Robotics and Automation for "Icebreaker". Issue 1 (14th November 2013) - Glass, B. J.; Dave, A.; McKay, C. P.; Paulsen, G.; Van, Michel; Wettergreen, David
<x xml:space="preserve">Abstract</x> The proposed "Icebreaker" mission is a return to the Mars polar latitudes first visited by the Phoenix mission in 2007–2008. Exploring and interrogating the shallow subsurface of Mars from the surface will require some form of excavation and penetration, with drilling being the most mature approach. A series of 0.5–5 m automated rotary and rotary‐percussive drills developed over the past decade by NASA Ames and Honeybee Robotics provide the capability to fly on a Mars surface mission within the next decade. Surface robotics have been integrated for sample transfer to deck instruments, and the Icebreaker sample acquisition system has been tested successfully in Mars chambers and analog field sites to depths between 1 and 3 m, most recently in the Antarctic Dry Valleys in January of 2013. This paper provides a hardware and software systems overview of the Icebreaker sample acquisition system, and discusses test results of this robotic system in relevant environments. Test results from recent Arctic and Antarctic field campaigns demonstrate a hands‐off "dust to data" capability.